International symposium on women in Asian fisheries (2001)
International Symposium on Women in Asian Fisheries presents a record of the 1998 symposium. The fisheries sector has unique problems related to women, which have to be addressed not only from a technical standpoint but also from a social one. The symposium is aimed at stimulating discussion and promoting well-planned research and development activities in this area.